Estimation of Fishing Ground Based on Distribution of Fishing Vessels and Oceanographic Factors in WPPNRI 573 - Panggabean, Donwill; Sudarmo, Agnes Puspitasari; Anwar, Kasful; Jalil, Jalil; Nazzla, Rauzatul (Politeknik Ahli Usaha Perikanan, 2023)
Fisheries Management Area of Republic of Indonesia (FMARI) 573 has great potential and needs to be supported by complete and accurate information, especially fishing ground locations so that the fisheries sector can become better. This study aims to estimate the location of the fishing ground in the western of FMARI 573 based on the movement of fishing vessels carrying out fishing operations, as well as sea surface temperature (SST) conditions and chlorophyll-a concentrations. The data used is a 10 year time series of AQUA-MODIS and SNPP-VIIRS satellite images. Analysis of chlorophyll-a and SST using ArcGis, while estimation of fishing ground locations with overlay techniques between ship distribution with SST conditions and chlorophyll-a concentrations. The results showed that the average SST value was relatively higher during Transitional Season I compared to the other three seasons. The average seasonal chlorophyll-a concentration fluctuates, the maximum value occurs in the Western Season and the minimum in the East Season. The concentration and distribution of fishing vessels indicate fishing ground areas in Pangandaran waters and along the coast of Binuangeun waters and Palabuhan Ratu Bay.